Tinjauan Ekonomi Islam Terhadap Bisnis Salon Muslimah Kota Medan - Zahrina Razali; N Nurasiah; N Nurlaila (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2019)
Muslimah salon means a beauty salon business which is run according to the elements of Islamic business. Not only the label but also the application and practice must also be based on Islamic teachings. This study is entitled An overview of the Islamic economy of the Muslim salon business in Medan. The purpose of this study is to explain how the Muslim salon business according to the Islamic economy, to explain the application and practice of Muslim salon in the city of Medan. The purpose of this study is to explain how the Muslim salon business according to the Islamic economy, to explain the application and practice of Muslim salon in the city of Medan. The study used a descriptive qualitative approach, the research subjects were determined through purposive sampling techniques. The object of this research is about the business of Muslim salon according to Islamic economics. While the subjects in this study were 3 salon owners and 5 informants who were each customer and salon employee. Data collection techniques are observation, interviews, and documentation. Data analysis techniques using data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that in the salon business applying the rules and practices of care in accordance with shariah, honest in managing the salon, reliable in terms of care, specifically for female consumers both Muslim and non-Muslim, do not accept male customers or employees, no conduct treatment practices that are prohibited in Islam, change the image of salons, closed places, prioritize halal and quality products, do not use illicit substances, provide religious care of this type based on ornate principles that are permitted in Islam, prioritize Islamic economic values in do business. The salon business labeled Muslim city of Medan in running its business is in conformity with what has been outlined by the criteria in the implementation of Islamic economics.